Comment on: “Split kinetic energy method for quantum systems with competing potentials”, Ann. Phys. 327 (2012) 2061 - Fernández, Francisco Marcelo (2018)
We show that the kinetic-energy partition method (KEP) is a particular example of the well known Rayleigh–Ritz variational method. We discuss some of the KEP results and compare them with those coming from other approaches.